NUTRITION EDUCATION: IMPLEMENTING APPLIED SCIENCE TO IMPROVE NUTRITIONAL KNOWLEDGE AMONG ADOLESCENTS AT SMA 1 INDRALAYA UTARA - Puji Amalliyah; Putri Inrian Tari; Fitria Aulia; Rahmi Fitri J.; Fildzah Hashifah Taufiq; Ayu Prameswari; Jafar Arifin (Fakultas Sains dan Teknologi, 2026)
Nutritional problems among adolescents in Indonesia, such as anemia and obesity, are often rooted in unhealthy eating patterns and exposure to misinformation. This community service activity aimed to improve the nutritional knowledge and literacy of adolescents at SMA Negeri 1 Indralaya Utara through the implementation of applied science. The method employed was an interactive multimedia-based counseling session with a quantitative evaluation design using pre-test and post-test instruments on 33 grade XI.1 students. The results of the activity showed a significant increase in knowledge, where students were actively engaged in critical discussions regarding health myths, product claims, and viral nutritional issues on social media. An interesting finding indicated that although the students possessed adequate initial knowledge, they still required reinforcement to filter the ambiguous information in the digital space. The main conclusion of this activity was that the counseling successfully strengthened the students' nutritional knowledge significantly, particularly in clarifying various misconceptions on social media. With a sharper understanding, students were expected to be able to apply balanced nutrition guidelines consistently and serve as positive agents of change for their peers within the school environment